Cork - Gil, Luis; Moiteiro, Cristina (Ullmann's Encyclopedia of Industrial Chemistry, 2000)
The article contains sections titled: 1.Introduction1.1.Definition and Origin1.2.History1.3.Morphology1.3.1.Microscopic Aspects1.3.2.Macroscopic Aspects1.4.Chemical Composition1.4.1.Suberin1.4.2.Lignin1.4.3.Polysaccharides1.4.4.Waxes1.4.5.Tannins1.4.6.Other Components1.5.Physical and Mechanical Properties2.Cork Extraction3.Production of Cork Based Products3.1.Disks and Cork Stoppers3.2.Granulates and Broken3.3.Composition Cork3.3.1.Floor and Wall Coverings3.3.2.Agglomerated Disks and Cork Stoppers3.3.3.Corkrubber3.4.Insulation Corkboard3.5.Other Specific Products4.Uses4.1.Stoppers4.2.Civil Construction4.3.Industrial Applications4.4.Automotive Industry4.5.Other Specific Uses5.Quality and Standardization5.1.Standardization and Testing5.2.Quality in Cork Production6.Economic Aspects6.1.Forestall Production6.2.Personnel and Companies6.3.Consumption of Products and Markets6.4.Producers7.Environmental and Toxicological Aspects7.1.Industrial Wastes7.2.Recycling and Treatments7.3.Emissions8.Legal Aspects
The following values have no corresponding Zotero field: periodical: Ullmann's Encyclopedia of Industrial Chemistry electronic-resource-num: 10.1002/14356007.f07_f01
Keywords: composition (voyant); Cork; insulation; products; stoppers